Biopanel identifies expression status of targetable proteins in sinonasal melanoma. (July 2016) - Grünmüller, Lisa; Thierauf, Julia; Weissinger, Stephanie E; Bergmann, Christoph; Bankfalvi, Agnes; Veit, Johannes; Hoffmann, Thomas K; Möller, Peter; Lennerz, Jochen K
Background: Advanced stage at presentation, lack of BRAF mutations and overall rarity pose unique challenges to the therapy and trial design in sinonasal melanoma.Methods: Here, we assessed the expression status of 12 proteins in two independent cohorts of sinonasal melanoma (n = 20).Results: Each case showed expression of at least one protein (KIT, TP53, MYC, HER2, EGFR, MET, VEGFR, BRAF V600E and/or MDM2), whereas lack of ALK, FLI1 and PDGFRα expression underscores differences to cutaneous melanoma. Comparison of marker frequencies to a metareview of the literature indicates that MYC, HER2, EGFR and MET had not been previously assessed.Conclusion: Expression of at least one potentially targetable protein per case illustrates proteome pathway profiling as one starting point for marker stratified trial design.